From Welfare State to Power State: Public Policy Transformation Under the Shadow of Oligarchy and Shadow Government in Indonesia - Ramadha Yanti Parinduri; Khairuddin Tampubolon; Pin Pin; Nunti Sibuea; Gunawan Undang (UIN Sunan Gunung Djati, 2025)
Indonesia is experiencing a shift from a welfare state to a power state, where public policies are increasingly influenced by oligarchs and shadow governments. This study uses qualitative methods, namely: 1) Using descriptive-critical analysis to understand the phenomenon of public policy shifts; 2) Examining the role of political and economic actors in shaping state policies. This study analyzes the transformation with a qualitative approach through literature study and public policy analysis. The results show that the dominance of elite groups in decision-making hinders democratization, exacerbates social inequality, and reduces government transparency. The implications of this research are: 1) Theoretical Implications, namely: a) Development of State Theory and Public Policy; b) Criticism of Democracy and Welfare Theory; c) Contribution to the Study of Governance and Political Corruption. 2) Practical Implications, namely: a) Policy Recommendations for the Government; b) Increasing Community and Civil Society Participation; c) Improvement of the Legal System and Anti-Corruption Enforcement; d) Reform of Political Parties and the Electoral System. The solutions offered by the author are: 1) Increasing Transparency and Accountability of Government; 2) Strengthening Democracy and Community Participation; 3) Public Policy Reform for People's Welfare; 4) Suppressing the Domination of Oligarchs and Shadow Government; 5) Strengthening the Legal System and Rule Enforcement. With these solutions, it is hoped that the transformation of public policy can be oriented back to the welfare of the people, not only to the interests of the ruling elite.